Green synthesis of silver nanoparticles using Ageratum conyzoides for activated carbon compositing to prepare antimicrobial cotton fabric - Thepsiri Jaruwan; Audtarat Sasiporn; Dasri Thananchai (Nanotechnology Reviews)
Wearing socks or shoes for an extended time can result in the growth of microorganisms and associated foot odor, which affects foot hygiene. Therefore, the development of an antimicrobial cloth layer is needed to prevent these odors. In this work, silver nanoparticles (AgNPs) are prepared using Ageratum conyzoides leaf extract mixed with hemp-activated carbon (HAC) (AgNPs-HAC) coated on cotton fabric (CF) surfaces. CFs were modified using a plasma technique to improve AgNP adherence (PCFs) (PCFs@HAC-AgNPs). The prepared AgNPs and sheets of PCFs@HAC-AgNPs were evaluated for the formation of AgNPs by ultraviolet–visible spectroscopy, surface morphology and particle size by transmission electron microscopy and field emission scanning electron microscopy, and crystallinity by X-ray diffraction. The result showed that AgNPs had a crystalline structure and uniform distribution on PCFs@HAC-AgNP sheets. The antimicrobial activity of PCFs@HAC-AgNP sheets was tested against Staphylococcus aureus and Bacillus subtilis bacteria that cause foot odor. All sheets showed strong antibacterial activity against both bacteria. Additionally, the sheets were evaluated for antimicrobial durability after washing. Although the sheets underwent numerous washing cycles, their antibacterial performance was retained with low environmental impact. These results indicate that PCFs@HAC-AgNP sheets can be used in the development of odor-reducing materials for shoes that can be laundered and reused.